Correlation between Students’ Vocabulary Mastery and Their Reading Comprehension: A Study in Grade 10 of Junior High School in SMAN 1 Junjung Sirih - Ivanium Basmai; Edi Trisno (Universitas Negeri Padang, 2022)
Correlational research was employed in this study. The participants in this study were the first-graders at SMAN 1 Junjung Sirih during the 2022–2023 academic year. There are 29 students in the sample. In this final study, the researcher's major aim was to find a relationship between students' reading comprehension skills and their vocabulary mastery. The data collection techniques used were as follows: first, collecting data from students' vocabulary tests and reading comprehension tests; second, computing and classifying the students' vocabulary mastery tests and reading comprehension; third, analyzing the students' vocabulary and reading comprehension scores; and finally, drawing conclusions based on the data. Based on the normality test results for the vocabulary and reading comprehension test scores, a significance value of 0.20 can be calculated, indicating that the data is normally distributed. The linearity significance score is.0 based on the linearity test, and the variation from linearity significance is.2. This indicates that the two variables are related. Linear. The Pearson product-moment correlation coefficient was used to examine the link between students' vocabulary mastery (as determined by a vocabulary test) and reading comprehension (as determined by a reading comprehension test). To make sure that the assumptions of normality and linearity were not broken, preliminary analysis was done. Higher perceived control scores were linked to higher reading test results (r = -.96, n = 29, p.001), indicating a significant positive correlation between the two variables.